The internet and various social media platforms as source of information to patients with wounds in Kenya - Adegu William; Angela Muoki; Benjamin Wabwire; Loise Kahoro; Protus Kituyi; Stanley Khainga; Ferdinand Nang'ole (JPRAS Open, 2024)
ABSTRACT: Background: The internet has led to the realization that the world is a global village. Due to technological advancements, anyone can access the internet and various video sharing platforms and in turn, get access to or share information across the world. One of the most sought-after critical pieces of information on the internet, as well as social media platforms, is information regarding wounds. Objective: To determine the views of patients with chronic wounds regarding the internet and other social media platforms as a source of information regarding wounds. Methodology: A descriptive prospective study covering the period between November 1, 2022, and January 30, 2023. All patients with chronic wounds presenting in the plastic outpatient clinic, together with patients presenting themselves in the wound clinic at Kenyatta National Hospital (KNH) during this period, were informed about the study and asked to participate. After consenting, they were then required to sign an informed consent form after agreeing to participate. Data collection was done through interviews and filled out in structured questionnaires. Data points included demographics, information on internet use, and interaction with the various social media platforms. Results: 83.4% of the participants were of the opinion that the contents shared were done so by professionals, compared to 12.5% who indicated that the owners or uploaders of the contents were laymen. 2.6% and 1.5%, on the other hand, opined that the owners or uploaders of the contents were unknown and difficult to tell, respectively. Discussion: The participants in the current study felt that some aspects regarding content on wounds that is shared on the internet as well as other social media platforms would need further improvement. Such areas included information regarding wound dressing concepts, the etiology and pathophysiology of wounds, complications of wounds, and wound pain management.